Strategic control over the effectiveness of state support measures for the defense industry under sanctions restrictions - I. F. Vetrova (Учёт. Анализ. Аудит)
Under the conditions of military conflict and severe sanctions pressure, the defense industrial complex (DIC) ensures Russia’s national security by producing modern weapons, military and special equipment and equipping the Armed Forces and military formations located in the zone of special military operation (SMO). One of the tasks facing the organizations of the industry is to achieve technological independence, its innovative development, preservation of leadership in the development and production of new and advanced models, complexes and systems of weapons, military and special equipment. It seems that this task can be solved with the active participation of the state. The purpose of the study is to develop a methodological toolkit for strategic control of the effectiveness of measures of state support of the defense industry organizations based on the analysis of the State Program “Development of the defense industry complex”. In the process of work such general scientific methods of cognition as observation, analysis, generalization; system analysis and synthesis were used. This article substantiates the necessity of reorientation of control from subsequent to strategic. The author’s approach to the definition of “strategic control” is proposed. The directions for the development of strategic control over the effectiveness of measures of state support of defense industry organizations in the conditions of sanctions restrictions are defined. The author’s system of indicators, supplementing those already built into the analyzed state program, which can be used in the strategic control of state support measures under sanctions, is recommended. The results of the study are intended for a wide range of readers, including representatives of authorized executive authorities in the development of normative, methodological, and information-analytical support of strategic control of the effectiveness of measures of state support of the defense industry in order to achieve the goals defined by the relevant documents.